Bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane for high-energy density battery and preparation method of bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane
By introducing bismuth halide oxide material into the solid electrolyte membrane, the transformation of PVDF to the β phase is promoted, and the problems of low conductivity of PVDF and uncontrollable lithium dendrites are solved, the electrochemical performance and cyclic stability of the battery are improved, and it is suitable for high-voltage and high-energy density batteries.
Patent Information
- Application Number
- CN202510169344.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-04
AI Technical Summary
When existing PVDF is a solid polymer electrolyte, the room temperature conductivity is low, lithium dendrites are uncontrollable, and it is difficult to be suitable for high voltage environments, affecting the battery cycling performance.
The solid electrolyte membrane of bismuth halide-polyvinyl fluoride composite is adopted to introduce bismuth halide material into the electrolyte membrane to adjust the nucleation process of PVDF, promote its transformation to the β phase with the highest dielectric constant, reduce the activation energy of lithium ion migration, and improve conductivity and cycling performance.
It significantly improves the ion conductivity and lithium ion migration number of the electrolyte, enhances the electrochemical performance and cyclic stability of the battery, and adapts to the application of high-voltage and high-energy-density batteries.
Smart Images

Figure BDA0005273439820000141 
Figure BDA0005273439820000151 
Figure BDA0005273439820000152
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a bismuth halide oxide-polyvinylidene fluoride composite solid electrolyte membrane for high energy density batteries and a preparation method thereof. Technical Background
[0002] Solid-state lithium batteries (SSLBs) have attracted much attention due to their high safety and excellent stability. As the core component of SSLBs, solid electrolytes play a vital role in ion conduction and battery safety. Compared with liquid electrolytes, solid electrolytes (CSEs) effectively inhibit the growth and spread of lithium dendrites, improve battery safety and extend battery life due to their rigidity, electrochemical stability, non-volatility and thermal stability. At present, solid electrolytes are mainly divided into two categories: solid inorganic electrolytes (SIs) and solid polymer electrolytes (SPEs). The polymers used for SPEs include polyoxides (PEO), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), etc. Compared with SIs, SPEs have good interface compatibility, excellent flexibility and the advantages of large-scale manufacturing, and are promising candidates for high-energy lithium metal batteries (LMBs). Therefore, SPEs can play a key role in overcoming the challenges of dendrite growth and interfacial parasitic reactions in LMBs.
[0003] Among various SPEs, PVDF has attracted much attention due to its excellent electrochemical stability, good thermodynamic properties and good stability to lithium metal. However, since PVDF is a non-ionic conductive polymer, its molecular structure lacks channels that can effectively conduct lithium ions. Although PVDF has a certain mechanical strength, it is not enough to completely suppress the tendency of lithium dendrites to penetrate the electrolyte layer. Therefore, when PVDF is used as a solid polymer electrolyte, the room temperature conductivity is often low and the lithium dendrites are uncontrollable. Especially when used in high-energy density batteries, the high-voltage environment will not only further accelerate the growth of lithium dendrites, but may also cause PVDF oxidation or decomposition, thereby affecting the ionic conductivity and battery cycle performance.
[0004] To solve these problems, one solution is to introduce inorganic fillers into PVDF. However, even with the introduction of inorganic fillers, when PVDF is used as SPE, the ionic conductivity at room temperature is still low, and it is difficult to solve the problem of lithium dendrite growth. At the same time, the introduction of inorganic fillers cannot inhibit the decomposition of PVDF in a high-voltage environment, resulting in the solid electrolyte composed of inorganic fillers and PVDF being difficult to apply to high-voltage positive electrodes such as ternary NMC and lithium cobalt oxide LCO, thereby limiting the application of PVDF. Therefore, there is an urgent need for a solid electrolyte that can improve room temperature conductivity while inhibiting the growth of lithium dendrites, improving battery cycle performance, and adapting to high-voltage and high-energy density batteries. Summary of the invention
[0005] The present invention aims at the problems in the prior art and proposes a bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane for high energy density batteries, which solves the problems that PVDF as a solid polymer electrolyte has low room temperature conductivity, uncontrollable lithium dendrites, and is difficult to be applied in high voltage environments.
[0006] In a first aspect, the present invention provides a bismuth halide oxide-polyvinylidene fluoride-based composite solid electrolyte membrane for a high energy density battery, wherein the raw materials thereof include a polymer containing polyvinylidene fluoride segments, bismuth halide oxide, and lithium salt;
[0007] The bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane for high energy density batteries has a β-phase content higher than 57% and a crystallinity selected from 23% to 28%.
[0008] As a further solution, the β-phase content of the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane for high energy density batteries is selected from 57% to 77%.
[0009] As a further solution, the general formula of the bismuth oxide halide is BiOX, wherein Bi is a bismuth element, O is an oxygen element, X is a halogen element, the halogen element is selected from any one of Cl, Br, I, and F, and the bismuth oxide halide is selected from any one of BiOF, BiOCl, BiOI, and BiOBr.
[0010] As a further solution, the oxidation potential of the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane is greater than or equal to 4.5V.
[0011] As a further solution, the oxidation potential of the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane is greater than or equal to 4.6V.
[0012] As some preferred solutions, the oxidation potential of the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane is greater than or equal to 4.7V.
[0013] As a further solution, the shape of the bismuth halide oxide can be selected from any one of zero-dimensional nanoparticles, one-dimensional nanowires, two-dimensional nanosheets, nanoflowers, and nanospheres. Among them, nanoflowers refer to the bismuth halide oxide prepared by the present invention presenting a spherical morphology of sheet-like clusters.
[0014] As a further solution, the bismuth halide oxide may preferably be in the shape of nanoflowers.
[0015] As a further embodiment, the polymer containing polyvinylidene fluoride chain segments is selected from polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and a mixture of polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0016] As a further solution, in the mixture of PVDF and PVDF-HFP, the mass ratio of PVDF to PVDF-HFP is selected from 3:1.
[0017] As a further solution, the mass ratio of the polymer containing polyvinylidene fluoride segments to the bismuth halide oxide is selected from the range of 1: (0.015-0.63).
[0018] As a further solution, the mass ratio of the polymer containing polyvinylidene fluoride segments to the bismuth oxide halide is selected from the range of 1:(0.1-0.4).
[0019] As a further solution, the mass ratio of the lithium salt to the polymer containing polyvinylidene fluoride segments is selected from (0.5-1.5):1.
[0020] As a further scheme, the lithium salt is selected from lithium hexafluorophosphate (LiPF6), lithium fluoride (LiF), lithium difluorooxalatoborate (LiODFB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium chloride (LiCl), lithium sulfate (Li2SO4), lithium acetate (LiOAc), lithium nitrate (LiNO3), lithium difluorophosphate (LiPO2F2), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium carbonate (Li2CO3), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalate)borate (LiBOB), and any one or more thereof.
[0021] As a further embodiment, the lithium salt is selected from LiTFSI.
[0022] As a further solution, the precursor solution of the PVDF-based composite solid electrolyte also includes an organic solvent.
[0023] As a further solution, the organic solvent is selected from any one or more of amide solvents, pyrrolidone solvents, and ether solvents.
[0024] As a further embodiment, the mass ratio of the organic solvent to the polymer containing polyvinylidene fluoride segments is selected from (5-20):1.
[0025] As a further solution, the thickness of the bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane for high energy density batteries is selected from 35 μm to 70 μm.
[0026] In a second aspect, the present invention also provides a method for preparing a bismuth halide oxide-polyvinylidene fluoride composite solid electrolyte membrane for a high energy density battery, comprising the following steps:
[0027] S1: dispersing a polymer containing a polyvinylidene fluoride segment, a lithium salt, and a bismuth halide oxide in an organic solvent according to a mass ratio to obtain a mixed solution;
[0028] S2: The mixed solution is coated and vacuum dried to obtain a PVDF-based composite solid electrolyte.
[0029] As a further preferred scheme, in step S1, according to the mass ratio, the polymer containing the polyvinylidene fluoride chain segment is first dissolved in an organic solvent, and then a lithium salt is added. After mixing evenly, bismuth halide oxide is further added. The step-by-step addition method helps to ensure sufficient dissolution and mixing of the solute, thereby obtaining a PVDF-based composite solid electrolyte with more orderly cross-linking and more uniform distribution of bismuth halide oxide.
[0030] As a further solution, in step S1, the dispersion temperature is selected from 35-50°C, and the dispersion time is selected from 12 hours and above.
[0031] As a further preferred solution, in step S1, the dispersion temperature is selected from 40°C-50°C, and the dispersion time is selected from 12h-16h.
[0032] As a further solution, in step S1, the dispersion method is not limited in principle, and the technician can choose any method such as ultrasound or stirring to disperse the polymer containing polyvinylidene fluoride segments, lithium salt, and bismuth halide oxide in the organic solvent.
[0033] As a further solution, when the solute is dispersed by stirring, the stirring speed is selected from 300 rpm to 700 rpm.
[0034] As a further solution, before coating the mixed solution in step S2, ultrasound is first performed to further promote the dispersion of the polymer containing polyvinylidene fluoride segments, lithium salt, and bismuth halide oxide in the organic solvent.
[0035] As a further solution, the ultrasonic step is to ultrasonicate for 8-12 minutes each time, let it stand for 1-3 minutes, and then repeat the ultrasonication and standing process, wherein the total ultrasonication time is greater than or equal to 0.5 hours.
[0036] As a further solution, in step S3, the coating method is not limited in principle, and the technicians can select a corresponding coating method according to the needs, such as mechanical coating.
[0037] As a further solution, the mechanical coating step is: pouring solution 3 on a glass plate, and then adjusting the scraper thickness to 300 um for uniform coating.
[0038] As a further solution, after coating, curing is performed for 1.5h-3h.
[0039] As a further solution, the vacuum drying temperature in step S2 is selected from 60°C-80°C.
[0040] As a further solution, the vacuum drying time in step S2 is selected to be greater than or equal to 20 hours.
[0041] As a further scheme, the preparation steps of the bismuth halide oxide are: according to the stoichiometric ratio, bismuth salt and concentrated nitric acid are dissolved in deionized water to obtain solution 1, halide is dissolved in deionized water to obtain solution 2, solution 2 is mixed with solution 1 for reaction, and after washing, drying and grinding, bismuth halide oxide is obtained.
[0042] As a further solution, the bismuth salt is selected from any one of oxygen-containing acid bismuth salts and organic acid bismuth salts.
[0043] As a further embodiment, the bismuth halide oxide is prepared at 15°C-30°C.
[0044] As a further embodiment, the halide is selected from any one of an organic covalent halide and an inorganic covalent halide.
[0045] As a further embodiment, the mass ratio of the bismuth salt to the halide is selected from (1-5): (2-3).
[0046] As a further solution, the mass ratio of the concentrated nitric acid to the bismuth salt is selected from 0.0125-0.125.
[0047] As a further solution, the volume ratio of the concentrated nitric acid to deionized water is selected from 0.025-0.125.
[0048] As a further solution, the time for the mixing reaction of solution 2 and solution 1 is selected from 6h-10h.
[0049] On the third aspect, the present scheme also proposes a high energy density battery, including a bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane.
[0050] Fourthly, this solution also proposes an energy storage device composed of a plurality of high energy density batteries for storing and releasing electrical energy.
[0051] Compared with the prior art, the present invention has at least the following beneficial effects:
[0052] (1) The bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane prepared by the present invention has a wide range of applicability, can stably operate at room temperature, high temperature and high voltage positive electrode environment, and provides a relatively wide electrochemical window to adapt to a variety of working conditions.
[0053] (2) The bismuth halide oxide material introduced in the present invention has good plasticity, and can obtain structures of different forms including one-dimensional, two-dimensional and three-dimensional by adjusting the preparation process. These different structural forms show significant optimization effects on electrochemical performance, further improving the overall performance of the electrolyte membrane.
[0054] (3) In the present invention, the interaction between the bismuth halide oxide material and PVDF plays a key role in the phase transformation process, and the formation of pores during the phase change of PVDF is effectively suppressed through competitive phase transformation. In addition, the distribution of the bismuth halide oxide material on the membrane surface helps to block some pores, thereby effectively reducing the porosity and pore size of the PVDF membrane and optimizing the compactness of the membrane.
[0055] (4) In the present invention, the uniform interaction between the bismuth oxide halide material as an inorganic filler and PVDF helps to change the nucleation process of PVDF and promote its transformation to the β phase with the highest dielectric constant. This process also reduces the crystallinity of PVDF, thereby reducing the Li + The activation energy of migration significantly improves the ionic conductivity of the electrolyte and the number of lithium ion transference, effectively improving the overall electrochemical performance of the battery.
[0056] (5) In the present invention, the interaction between the bismuth oxide halide material and PVDF promotes the occurrence of the dehydrofluorination reaction of PVDF, which is beneficial to the formation of carbon-carbon double bonds during the cycle. - The ions help to form abundant LiF at the electrolyte-electrode interface, which in turn forms a stable solid electrolyte interface (SEI) layer at the interface, improving the long-cycle stability of the battery.
[0057] (6) The composite solid polymer electrolyte designed in the present invention aims to improve the interfacial stability of the battery and has the advantages of simple process, short production cycle, low cost and environmental protection. It is suitable for being widely used in lithium-ion batteries and meets the needs of large-scale commercial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0059] Figure 1 It is the SEM picture of comparative example 1, embodiment 2, 3, wherein Figure 1 a is the SEM image of Comparative Example 1, Figure 1 b is the SEM image of Example 3, Figure 1 c is the SEM image of Example 2;
[0060] Figure 2 middle, Figure 2 a is a comparison chart of XRD data of Example 1 and Comparative Example 1, Figure 2 b is a comparison chart of FTIR data of Example 1 and Comparative Example 1;
[0061] Figure 3 The Li||Li symmetric battery prepared in Example 1 was cycled at 0.1 mAh cm -1 The XPS spectrum fitting diagram obtained after 100 cycles under current density, where Figure 3 a is the peak diagram of O1s before the cycle, Figure 3 b is the peak diagram of O1s after cycling. Figure 3 c is the peak diagram of F1s before the cycle, Figure 3 d is the peak diagram of F1s after cycling;
[0062] Figure 4 is the SEM image of two-dimensional BiOCl nanosheets, where Figure 4 SEM image of two-dimensional BiOCl nanosheets when a is 100 μm. Figure 4 b is the SEM image of two-dimensional BiOCl nanosheets at 2 μm. Figure 4 c is the SEM image of two-dimensional BiOCl nanosheets at 1 μm;
[0063] Figure 5 This is the SEM image of three-dimensional BiOCl nanoflowers, where Figure 5 a is the SEM image of three-dimensional BiOCl nanoflowers at 50 μm. Figure 5 b is the SEM image of three-dimensional BiOCl nanoflowers at 10 μm. Figure 5 c is the SEM image of three-dimensional BiOCl nanoflowers at 5 μm;
[0064] Figure 6 The electrochemical window diagrams of Example 1 and Comparative Example 1 are shown;
[0065] Figure 7 This is a comparison chart of ionic conductivity of Example 1 and Comparative Example 1 at 25°C;
[0066] Figure 8 This is a comparison diagram of activation energies of Example 1 and Comparative Example 1;
[0067] Fig. 9 0.5C cycle performance diagram of Example 1;
[0068] Fig.10 This is the cycle performance diagram of Example 1 and Comparative Example 1 at a 0.2C rate. DETAILED DESCRIPTION
[0069] For ease of understanding, the present invention will be described in more detail below and examples of the present invention are given, but the scope of the present invention is not limited thereby.
[0070] The following is a description of terms or words, and unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0071] Herein, the term "crystallinity" refers to the percentage of the crystalline region in the bismuth oxyhalide-polyvinylidene fluoride based composite solid electrolyte membrane relative to the volume or mass of the entire material.
[0072] In this article, the term "β phase" refers to a crystalline form of PVDF in the bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane, which belongs to the TGTG type conformation, in which each unit cell contains two polymer chains, the directions of the dipole moments in the molecular chains are opposite, and the net dipole moment is zero.
[0073] In this article, the term "α phase" refers to a crystalline form of PVDF in the bismuth halide-polyvinylidene fluoride composite solid electrolyte membrane, which is composed of repeated TTTT conformation units, and the dipole moments on adjacent molecular chains are perpendicular to the main chain of the molecular chain and in the same direction.
[0074] In a first aspect, the present invention provides a bismuth halide oxide-polyvinylidene fluoride-based composite solid electrolyte membrane for a high energy density battery, wherein the raw materials thereof include a polymer containing polyvinylidene fluoride segments, bismuth halide oxide, and lithium salt;
[0075] The bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane for high energy density batteries has a β-phase content higher than 57% and a crystallinity selected from 23% to 28%.
[0076] In order to solve the problems of poor synergy between the existing inorganic fillers introduced into PVDF and PVDF, insufficient cycle stability, low room temperature ionic conductivity, and difficulty in applying to high-voltage positive electrodes, the present invention introduces bismuth halide oxide into the precursor solution of bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane. During the curing process, since the bismuth halide oxide material competes with the phase change process of the polymer containing polyvinylidene fluoride chain segments, the presence of the bismuth halide oxide material helps to limit or interfere with the crystal transformation of the polymer containing polyvinylidene fluoride chain segments, thereby limiting the generation of pores in the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane. ; At the same time, the bismuth halide oxide material distributed on the surface of the membrane also helps to block some pores, thereby reducing the pore size and porosity of the PVDF polymer membrane, inhibiting the growth of lithium dendrites, and reducing the resistance to lithium ion migration; secondly, the presence of bismuth halide oxide also helps to change the nucleation process of PVDF, reduce the crystallinity of the polymer containing polyvinylidene fluoride segments, and promote the polymer containing polyvinylidene fluoride segments to transform to the β phase with the highest dielectric constant; when the β phase content is higher than 57% and the crystallinity meets 23%-28%, the bismuth halide oxide-polyvinylidene fluoride composite solid electrolyte membrane used for high energy density batteries can better reduce Li + Migration activation energy, improve the ionic conductivity of the electrolyte and the number of lithium ion migration, and achieve the effect of improving battery performance; finally, Figure 2 b. Figure 3 As shown, the bismuth halide oxide introduced into the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane can also promote the dehydrofluorination phenomenon in the polymer containing polyvinylidene fluoride groups during the battery cycle. The fluoride ions released can form LiF on the interface SEI, further improving the stability of the SEI layer and avoiding the decomposition of the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane in a high voltage environment, thereby improving the long cycle performance of the battery and widening the electrochemical window (such as Figure 6 ); at the same time, under high potential conditions, bismuth halide oxide can also serve as a physical barrier to reduce or prevent direct contact between active ions and the electrode surface, thereby inhibiting the occurrence of side reactions; therefore, under the interaction between the polymer containing polyvinylidene fluoride chain segments and bismuth halide oxide, the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane proposed in the present invention has good cycle performance and room temperature ionic conductivity, and is particularly suitable for high energy density batteries.
[0077] As a further solution, the β-phase content of the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane for high energy density batteries is selected from 57% to 77%.
[0078] As some optional parameters, the general formula of the bismuth oxide halide is BiOX, wherein Bi is a bismuth element, O is an oxygen element, X is a halogen element, and the halogen element is selected from any one of Cl, Br, I, and F, and the bismuth oxide halide is selected from any one of BiOF, BiOCl, BiOI, and BiOBr.
[0079] As some optional parameters, the oxidation potential of the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane is greater than or equal to 4.5V.
[0080] As some preferred parameters, the oxidation potential of the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane is greater than or equal to 4.6V.
[0081] As some preferred parameters, the oxidation potential of the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane is greater than or equal to 4.7V.
[0082] As some optional parameters, the shape of the bismuth oxide halide is not limited in principle, for example, it can be selected from zero-dimensional nanoparticles, one-dimensional nanowires, two-dimensional nanosheets (such as Figure 4 ), nanoflowers, and nanospheres. Among them, nanoflowers refer to bismuth halide oxide prepared by the present invention with a spherical morphology of sheet-like clusters (such as Figure 5 ).
[0083] As some optional parameters, the shape of the bismuth oxide halide may preferably be nanoflowers.
[0084] As some optional parameters, the polymer containing polyvinylidene fluoride segments is selected from polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and a mixture of polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0085] As some optional parameters, in the mixture of PVDF and PVDF-HFP, the mass ratio of PVDF to PVDF-HFP is selected from 3:1.
[0086] As some optional parameters, the mass ratio of the polymer containing polyvinylidene fluoride segments to the bismuth halide oxide is selected from the range of 1: (0.015-0.63).
[0087] As some optional parameters, the mass ratio of the polymer containing polyvinylidene fluoride segments to the bismuth halide oxide is selected from 1: (0.1-0.4). The mass ratio selected from 1: (0.1-0.4) helps to better exert the compounding effect between the bismuth halide oxide and the polymer containing polyvinylidene fluoride segments, adjust the crystallinity and pore structure of the polymer containing polyvinylidene fluoride segments, and thus optimize the cycle performance.
[0088] As some optional parameters, the mass ratio of the lithium salt to the polymer containing polyvinylidene fluoride segments is selected from (0.5-1.5):1.
[0089] As some optional parameters, the lithium salt is selected from any one or more of LiPF6, LiF, LiBF4, LiTFSI, LiCl, Li2SO4, LiOAc, LiNO3, LiPO2F2, LiCF3SO3, Li2CO3, LiFSI, LiBOB, and LiDFOB.
[0090] As some optional parameters, the lithium salt is selected from LiTFSI.
[0091] As some optional parameters, the precursor solution of the PVDF-based composite solid electrolyte also includes an organic solvent.
[0092] As some optional parameters, the organic solvent is selected from any one or more of amide solvents, pyrrolidone solvents and ether solvents.
[0093] As some optional parameters, the amide solvent is selected from any one or more of N,N-dimethylformamide (DMF), N,N-diethylformamide (DEMF), N,N-dimethylpropionamide (DMPA), N-methyl-N-ethylformamide (MEMA), N-ethyl-N-methylformamide (EMEA), N-phenylpropionamide (NPA), N-ethyl-N,N-dimethylformamide (EDMF), and N,N-dimethylphthalamide (DMPhF).
[0094] As some optional parameters, the pyrrolidone solvent is selected from N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N-butylpyrrolidone (NBP), N-isopropylpyrrolidone (NIP), N-octylpyrrolidone (NSP), N-hexadecylpyrrolidone (C 16 -Pyrrolidone), N-methyl-2-pyrrolidone (NMP-2), N,N-dimethyl-2-pyrrolidone (DM-2P) or any one or more thereof.
[0095] As some optional parameters, the ether solvent is selected from any one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), tetrahydrofuran (THF), dimethoxyethane (DME), ethoxyethane (EOE), ethylene oxide (EO), and phenyl ether.
[0096] As some optional parameters, the mass ratio of the organic solvent to the polymer containing polyvinylidene fluoride segments is selected from (5-20):1.
[0097] As some optional parameters, the thickness of the bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane for high energy density batteries is selected from 35 μm to 70 μm.
[0098] In a second aspect, the present invention also provides a method for preparing a bismuth halide oxide-polyvinylidene fluoride composite solid electrolyte membrane for a high energy density battery, comprising the following steps:
[0099] S1: dispersing a polymer containing a polyvinylidene fluoride segment, a lithium salt, and a bismuth halide oxide in an organic solvent according to a mass ratio to obtain a mixed solution;
[0100] S2: The mixed solution is coated and vacuum dried to obtain a PVDF-based composite solid electrolyte.
[0101] As a further preferred scheme, in step S1, according to the mass ratio, the polymer containing the polyvinylidene fluoride chain segment is first dissolved in an organic solvent, and then a lithium salt is added. After mixing evenly, bismuth halide oxide is further added. The step-by-step addition method helps to ensure sufficient dissolution and mixing of the solute, thereby obtaining a PVDF-based composite solid electrolyte with more orderly cross-linking and more uniform distribution of bismuth halide oxide.
[0102] As a further solution, in step S1, the dispersion temperature is selected from 35-50°C, and the dispersion time is selected from 12 hours and above.
[0103] As a further preferred solution, in step S1, the dispersion temperature is selected from 40°C-50°C, and the dispersion time is selected from 12h-16h.
[0104] As a further solution, in step S1, the dispersion method is not limited in principle, and the technician can choose any method such as ultrasound or stirring to disperse the polymer containing polyvinylidene fluoride segments, lithium salt, and bismuth halide oxide in the organic solvent.
[0105] As a further solution, when the solute is dispersed by stirring, the stirring speed is selected from 300 rpm to 700 rpm.
[0106] As a further solution, before coating the mixed solution in step S2, ultrasound is first performed to further promote the dispersion of the polymer containing polyvinylidene fluoride segments, lithium salt, and bismuth halide oxide in the organic solvent.
[0107] As some optional parameters, in the step S3, the ultrasonic step of solution 3 is 8-12 minutes per ultrasonication, standing for 1-3 minutes, and then repeating the ultrasonication and standing process, wherein the total ultrasonication time is greater than or equal to 0.5 hours. The method of first 8-12 minutes, then standing for 1-3 minutes, and cyclic ultrasonication and standing steps until the total ultrasonication time is greater than 0.5 hours helps to ensure that the bismuth halide oxide material is fully dispersed in the solution and avoids the occurrence of agglomeration, so that the bismuth halide oxide can better cooperate with the polymer containing polyvinylidene fluoride chain segments to reduce the pore size and porosity of the PVDF-based composite solid electrolyte.
[0108] As some optional parameters, in step S3, the coating method is not limited in principle, and the technicians can select the corresponding coating method according to the needs, such as mechanical coating.
[0109] As some optional parameters, the mechanical coating step is: pouring solution 3 on a glass plate, and then adjusting the scraper thickness to 300 um for uniform coating.
[0110] As a further solution, after coating, curing is performed for 1.5h-3h.
[0111] As some optional parameters, the vacuum drying temperature in step S2 is selected from 60°C-80°C.
[0112] As some optional parameters, the vacuum drying time in step S2 is selected to be greater than or equal to 20 hours.
[0113] On the third aspect, the present scheme also proposes a high energy density battery, including a bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane.
[0114] Fourthly, this solution also proposes an energy storage device composed of a plurality of high energy density batteries for storing and releasing electrical energy.
[0115] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0116] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0117] Example 1
[0118] Preparation of Bismuth Oxide Halide-Polyvinylidene Fluoride Composite Solid Electrolyte Membrane
[0119] Preparation of Nanoflowers
[0120] A simple BiOCl nanoflower structure was synthesized under the condition that the mass ratio of NH4Cl to Bi(NO3)3·5H2O was 3:1. At 25°C, 1g of Bi(NO3)3·5H2O and 4ml of concentrated nitric acid were added to 40ml of deionized water and stirred vigorously to obtain solution 1. Subsequently, 3g of NH4Cl was dissolved in 10mL of deionized water to obtain solution 2, and solution 2 was added to solution 1. After stirring for 8h, the suspension was collected and centrifuged at 5000rpm, and washed with deionized water and ethanol for 3 times, dried and ground under a vacuum environment at 333K to obtain BiOCl with a nanoflower structure, which was sieved through 200 mesh and stored in a glove box.
[0121] S1: PVDF and DMF were stirred at a speed of 500 rpm for 12 hours in a mass ratio of 1:10 to obtain a PVDF solution, which was marked as solution 1; LiTFSI was added to solution 1 and stirred at a speed of 500 rpm for 6 hours, which was marked as solution 2, wherein the mass ratio of LiTFSI to PVDF was 1:1;
[0122] S2: adding BiOCl to solution 2, stirring at 400 rpm for 12 hours at 45°C to obtain solution 3, wherein the mass ratio of BiOCl to PVDF is selected from 0.1:1;
[0123] S3: The uniformly mixed solution 3 is subjected to ultrasonic treatment, each time for 10 minutes, and then allowed to stand for 2 minutes, for a total of 30 minutes. After the ultrasonic treatment, the ultrasonicated solution 3 is poured onto a glass plate, and the scraper thickness is adjusted to 300um for coating. After the coating is completed, it is allowed to stand for 2h, and then vacuum dried at 70°C for 24h to obtain an oxidized bismuth halide-polyvinylidene fluoride composite solid electrolyte membrane for high energy density batteries. The thickness of the oxidized bismuth halide-polyvinylidene fluoride composite solid electrolyte membrane is 50um.
[0124] Preparation of the battery:
[0125] Stainless steel sheets are used as positive and negative electrodes respectively to assemble SS||SS batteries;
[0126] Li||SS battery is assembled using metallic lithium as negative electrode and stainless steel as positive electrode;
[0127] Use metallic lithium as positive and negative electrodes to prepare Li||Li symmetric batteries;
[0128] Li metal was used as the negative electrode and NCM811 as the positive electrode to prepare Li||NCM811 full battery. All operations were carried out in a glove box filled with argon.
[0129] Example 2
[0130] The synthesis method and preparation steps are the same as those in Example 1, except that BiOI is used instead of BiOCl.
[0131] Example 3
[0132] Preparation of 2D nanosheets
[0133] A simple BiOCl nanosheet structure was synthesized under the condition that the mass ratio of NH4Cl to Bi(NO3)3·5H2O was 1:3. At 25°C, 1g of Bi(NO3)3·5H2O and 3ml of concentrated nitric acid were added to 40ml of deionized water and stirred vigorously to obtain solution 1. Subsequently, 1g of NH4Cl was dissolved in 10nL of deionized water to obtain solution 2, and solution 2 was added to solution 1. After stirring for 8h, the suspension was collected and centrifuged at 5000rpm, and washed with deionized water and ethanol for 3 times, dried and ground under a vacuum environment at 333K to obtain a two-dimensional nanosheet structure of BiOCl, which was sieved through 200 mesh and stored in a glove box.
[0134] The synthesis method and preparation steps are the same as those in Example 1, except that BiOCl with a two-dimensional nanosheet structure is used to replace BiOCl with a nanoflower structure.
[0135] Example 4
[0136] Preparation of one-dimensional nanowires
[0137] A simple BiOCl nanosheet structure was synthesized under the condition that the mass ratio of KCl to Bi(NO3)3·5H2O was 3:1. At 25°C, 1g of Bi(NO3)3·5H2O and 2mL of concentrated nitric acid were added to 40mL of deionized water and stirred vigorously to obtain solution 1. Subsequently, 1g of KCl was dissolved in 10mL of deionized water to obtain solution 2, and solution 2 was added to solution 1. After stirring for 8h, the suspension was collected and centrifuged at 5000rpm, and washed with deionized water and ethanol for 3 times. It was dried and ground in a vacuum environment at 333K to obtain a one-dimensional nanowire structure of BiOCl, which was sieved through 200 mesh and stored in a glove box.
[0138] The synthesis method and preparation steps are the same as those in Example 1, except that BiOCl with a one-dimensional nanowire structure is used to replace BiOCl with a nanoflower structure.
[0139] Example 5
[0140] The synthesis method and preparation steps are the same as those in Example 1, except that the mass ratio of PVDF to BiOCl is 1:0.4.
[0141] Example 6
[0142] The synthesis method and preparation steps are the same as those in Example 1, except that the mass ratio of PVDF to BiOCl is 1:0.015.
[0143] Comparative Example 1
[0144] The synthesis method and preparation steps are the same as those in Example 1, except that BiOCl is not added.
[0145] Comparative Example 2
[0146] The synthesis method and preparation steps are the same as those in Example 1, except that MgO particles are used to replace the BiOCl with a nanoflower structure.
[0147] Comparative Example 3
[0148] The synthesis method and preparation steps are the same as those in Example 1, except that boron nitride nanosheets (BN) are used to replace the BiOCl with a nanoflower structure.
[0149] Comparative Example 4
[0150] The synthesis method and preparation steps are the same as those in Example 1, except that Al2O3 particles are used to replace the BiOCl with a nanoflower structure.
[0151] Comparative Example 5
[0152] The synthesis method and preparation steps are the same as those in Example 1, except that polyvinyl nitrile is used to replace PVDF.
[0153] Test Method
[0154] The electrochemical window of the electrolyte was determined by linear sweep voltammetry (LSV): Li||SS battery was used as the battery to be tested, with a voltage of 1 mV s -1 The scan rate is slowly scanned from the battery open circuit voltage to the positive voltage to obtain the electrochemical window.
[0155] Electrochemical impedance spectroscopy (EIS) was used to measure the ionic conductivity of the electrolyte. The SS||SS battery was used as the battery to be tested for electrochemical impedance spectroscopy, with a frequency range of 0.1-10 -6 Hz, amplitude 10mV. After the test, the battery was disassembled to measure the thickness of the solid electrolyte, and the electrolyte ion conductivity was calculated based on the AC impedance results.
[0156] Take the Li||Li symmetrical battery as the battery to be tested: the battery is subjected to constant current density charge and discharge test. The test conditions are to apply a certain current density to it, charge it for one hour, and then discharge it for one hour for a cycle.
[0157] Take Li||NCM811 full battery as the battery to be tested: the battery is charged and discharged cycled at a certain current density to explore the battery stability, where the voltage range is 3.0V-4.3V.
[0158] The test results are shown in Table 2
[0159] Table 1
[0160]
[0161]
[0162] Table 2
[0163]
[0164] From Examples 1-6 and Comparative Examples 1-5, it can be observed that Examples 1-6 exhibit better porosity and pore size than Comparative Examples 1-5, and at the same time have a higher β-phase ratio and better crystallinity; at the same time, after 100 cycles, Examples 1-6 exhibit a higher cycle capacity retention rate than Comparative Examples 1-5, indicating that the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane proposed in this scheme can effectively improve the battery conductivity and optimize the battery cycle performance.
[0165] Table 3
[0166] Chemical Bond Comparative Example 1 Example 1 CO 30% 18% C=O 45% 54% Li-F 20% 34%
[0167] From Examples 1 and 2 in Table 2 and Comparative Example 1, it can be observed that when no bismuth halide oxide is added, Figure 1 a. Figure 1 It can be observed that Comparative Example 1 exhibits a higher porosity than Example 2. At the same time, it can be seen from Table 2 that Comparative Example 1 has a worse porosity and pore size, as well as a β-phase content than Examples 1 and 2, thereby exhibiting a lower electrochemical performance ( Figure 6 , 7 , 8, 10), indicating that the compounding of BiOCl and the polymer containing polyvinylidene fluoride chain segments enhances the ion conductivity of the bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane, and plays an important role in optimizing the cycle performance of the bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane. At the same time, it can be observed from Table 3 that when BiOCl is not added, Comparative Example 1 has a lower Li-F bond content and C=O content, while after adding, under the interaction of BiOCl and the polymer containing polyvinylidene fluoride chain segments, Example 1 exhibits a higher Li-F bond content and C=O content, so Example 1 also exhibits better electrochemical performance.
[0168] Example 1 and Comparative Examples 2-4 reveal that not any addition of inorganic fillers can improve the performance of bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane. This may be because although the simple addition of inorganic fillers can optimize the battery's ion conductivity to a certain extent, due to the lack of interaction with the polymer containing polyvinylidene fluoride chain segments, the inorganic fillers added in Comparative Examples 2-4 cannot compete with the polymer containing polyvinylidene fluoride chain segments during the phase change process, causing the polymer containing polyvinylidene fluoride chain segments to transform toward the β phase. At the same time, the inorganic fillers in Comparative Examples 2-4 cannot promote the dehydrofluorination of the polymer containing polyvinylidene fluoride groups during the cycle process. Therefore, Comparative Examples 2-4 exhibit lower cycle performance than Example 1.
[0169] In Comparative Example 5 and Example 1, we further discussed the importance of polymers containing polyvinylidene fluoride chain segments for bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membranes. When polyvinyl nitrile was used to replace PVDF, the cycle performance of Comparative Example 5 was significantly lower than that of Example 1. This may be because polyvinyl nitrile lacks polyvinylidene fluoride groups, making it difficult to cooperate with BiOCl to inhibit the formation of lithium dendrites, optimize lithium ion migration resistance, and improve the stability of the SEI layer.
[0170] In Examples 1-2, we discussed the effects of different bismuth halide oxides on bismuth halide oxide-polyvinylidene fluoride composite solid electrolyte membranes. Figure 1 It can be observed that, regardless of whether BiOCl or BiOI is used, Examples 1-2 exhibit good pore structure and β-phase content. Fig. 9 ), Example 2 also has good initial discharge capacity and cycle capacity retention rate, indicating that different bismuth oxide halides can effectively cooperate with the polymer containing polyvinylidene fluoride chain segments, thereby optimizing the performance of the bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane.
[0171] Different shapes of bismuth oxide halides also have different effects on the performance of bismuth oxide halides-polyvinylidene fluoride based composite solid electrolyte membranes. It can be observed from Examples 1, 3-4 that compared with Examples 3 and 4, Example 1 with a nanostructure exhibits better pore structure and crystallinity. At the same time, after 100 cycles, Examples 1 and 3 exhibit better cycle performance than Example 4. This may be because compared with the one-dimensional nanowire structure, the two-dimensional nanosheet and nanoflower structure can form larger and more bismuth oxide halide / PVDF interface phases, thereby achieving faster Li +Transmission channel. At the same time, the structures of two-dimensional nanosheets and nanoflowers can reduce the crystallinity of PVDF polymers to a greater extent than the one-dimensional nanowire structure, thereby optimizing the cycle performance of Examples 1 and 3. Similarly, compared with the two-dimensional nanosheet structure, the nanoflowers with a spherical morphology of sheet-like clusters can better block the pores on the surface of the bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane, thereby reducing the porosity and optimizing the cycle performance. Therefore, Example 1 shows a better cycle capacity retention rate than Examples 3 and 4.
[0172] In order to further optimize the compounding effect of the polymer containing polyvinylidene fluoride chain segments and bismuth halide oxide, and improve the cycle performance of the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane, we further optimized the compounding content of the polymer containing polyvinylidene fluoride chain segments and bismuth halide oxide. It can be observed that in Examples 1, 5-6, when the mass ratio range of the polymer containing polyvinylidene fluoride chain segments to the bismuth halide oxide is selected from 1: (0.1-0.4), Examples 1 and 5 exhibit better cycle performance than Example 6. This may be because when the mass ratio range of the polymer containing polyvinylidene fluoride chain segments to the bismuth halide oxide is selected from 1: (0.1-0.4), it helps to better achieve the compounding effect of bismuth halide oxide and the polymer containing polyvinylidene fluoride chain segments, thereby optimizing the cycle performance.
[0173] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A bismuth halide oxide-polyvinylidene fluoride composite solid electrolyte membrane for high energy density batteries, characterized in that: The β-phase content of PVDF in the bismuth halide oxide-polyvinylidene fluoride composite solid electrolyte membrane for high energy density batteries is higher than 57%, the crystallinity is selected from 23%-28%, and the general formula of the bismuth halide oxide is BiOX, wherein Bi is a bismuth element, O is an oxygen element, and X is a halogen element, and the halogen element is selected from any one of Cl, Br, I, and F.
2. The bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane according to claim 1, characterized in that: The raw materials of the bismuth oxide halide-polyvinylidene fluoride composite solid electrolyte membrane include a polymer containing polyvinylidene fluoride chain segments, bismuth oxide halide, and lithium salt; Preferably, the bismuth oxide halide is selected from any one of BiOF, BiOCl, BiOI, and BiOBr; The shape of the bismuth oxide halide can be selected from any one of zero-dimensional nanoparticles, one-dimensional nanowires, two-dimensional nanosheets, nanoflowers, and nanospheres; Preferably, the bismuth halide oxide may be in the shape of nanoflowers.
3. The bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane according to claim 1, characterized in that: The polymer containing polyvinylidene fluoride chain segments is selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and a mixture of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene; Preferably, in the mixture of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene, the mass ratio of polyvinylidene fluoride to polyvinylidene fluoride-hexafluoropropylene is selected from 3:1; Preferably, the mass ratio of the polymer containing polyvinylidene fluoride segments to the bismuth halide oxide is selected from the range of 1: (0.015-0.63); Preferably, the mass ratio of the polymer containing polyvinylidene fluoride segments to the bismuth halide oxide is selected from the range of 1:(0.1-0.4); Preferably, the mass ratio of the lithium salt to the polymer containing polyvinylidene fluoride chain segments is selected from (0.5-1.5):
1.
4. The bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane according to claim 1, characterized in that: The lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium fluoride, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl imide), lithium chloride, lithium sulfate, lithium acetate, lithium nitrate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium carbonate, lithium bis(fluorosulfonyl imide), and lithium bis(oxalatoborate); Preferably, the lithium salt is selected from lithium bis(trifluoromethanesulfonyl imide).
5. The bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane according to claim 1, characterized in that: The precursor solution of the PVDF-based composite solid electrolyte also includes an organic solvent; Preferably, the organic solvent is selected from any one or more of amide solvents, pyrrolidone solvents, and ether solvents; Preferably, the mass ratio of the organic solvent to the polymer containing polyvinylidene fluoride segments is selected from (5-20): 1; Preferably, the thickness of the bismuth oxide halide-polyvinylidene fluoride based composite solid electrolyte membrane for high energy density batteries is selected from 35 μm to 70 μm.
6. A method for preparing the bismuth halide oxide-polyvinylidene fluoride based composite solid electrolyte membrane according to claim 1, characterized in that: The steps include: S1: dispersing a polymer containing a polyvinylidene fluoride segment, a lithium salt, and a bismuth halide oxide in an organic solvent according to a mass ratio to obtain a mixed solution; S2: The mixed solution is coated and vacuum dried to obtain a PVDF-based composite solid electrolyte.
7. The preparation method according to claim 6, characterized in that: In the step S1, the dispersion temperature is selected from 35-50°C, and the dispersion time is selected from 12 hours and above; Preferably, in step S1, the dispersion temperature is selected from 40°C-50°C, and the dispersion time is selected from 12h-16h; Preferably, in step S1, the polymer containing the polyvinylidene fluoride chain segment is first dissolved in an organic solvent according to the mass ratio, and then a lithium salt is added, and after mixing evenly, bismuth halide oxide is further added; Preferably, in step S2, the mixed solution is firstly ultrasonicated before coating; Preferably, the ultrasonic step is to ultrasonicate for 8-12 minutes, let stand for 1-3 minutes, and then repeat the ultrasonication and standing process, wherein the total ultrasonication time is greater than or equal to 0.5 hours; Preferably, after coating, curing is performed for 1.5h-3h; Preferably, the vacuum drying temperature in step S2 is selected from 60°C to 80°C; Preferably, the vacuum drying time in step S2 is selected to be greater than or equal to 20 hours.
8. The preparation method according to claim 6, characterized in that: The preparation steps of the bismuth halide oxide are as follows: according to the stoichiometric ratio, bismuth salt and concentrated nitric acid are dissolved in deionized water to obtain solution 1, halide is dissolved in deionized water to obtain solution 2, solution 2 is mixed with solution 1 for reaction, and the bismuth halide oxide is obtained after washing, drying and grinding.
9. The process for preparing bismuth halide oxide according to claim 8, characterized in that: The bismuth salt is selected from any one of an oxygen-containing acid bismuth salt and an organic acid bismuth salt; Preferably, the bismuth halide oxide is prepared at 15°C-30°C; Preferably, the halide is selected from any one of an organic covalent halide and an inorganic covalent halide; The mass ratio of the bismuth salt to the halide is selected from (1-5): (2-3); Preferably, the mass ratio of the concentrated nitric acid to the bismuth salt is selected from 0.0125-0.125; Preferably, the volume ratio of concentrated nitric acid to deionized water is selected from 0.025-0.125; Preferably, the mixing reaction time of the solution 2 and the solution 1 is selected from 6h-10h.
10. A diaphragm, an electrode, a battery, an electrochemical device, an electrical device, an energy storage device, characterized in that: A bismuth halide oxide-polyvinylidene fluoride composite solid electrolyte membrane comprising the bismuth halide oxide-polyvinylidene fluoride composite solid electrolyte membrane according to any one of claims 1 to 5 or a bismuth halide oxide-polyvinylidene fluoride composite solid electrolyte membrane prepared by the preparation method according to any one of claims 6 to 9; Preferably, the battery is selected from any one of a solid-state battery and a semi-solid-state battery.
Citation Information
Patent Citations
Bismuth oxyhalide aqueous zinc ion secondary battery positive electrode and preparation method and application thereof
CN110416531A
Solid polymer electrolyte and preparation method and application thereof
CN114678589A
Method for modifying bismuth oxyiodide-based composite solid polymer electrolyte and method for constructing lithium battery by using bismuth oxyiodide-based composite solid polymer electrolyte
CN119069819A
Solid electrolyte membrane and single cell for solid oxide fuel cell including the same
JP2016081919A
Cited By
High-interfacial-compatibility nano silicon dioxide composite polymer electrolyte as well as preparation method and application thereof
CN120767400A
High interfacial compatibility nanosilica composite polymer electrolyte, preparation method and application thereof
CN120767400B